Efektivitas Penerapan Model Pembelajaran Realistic Mathematics Education terhadap Pemahaman Konsep untuk Meningkatkan Kemampuan Komunikasi Matematika - Agnes Alfi Khairuni Sirait; Asrifah Siahaan; Daniel Samosir; Della Permata Rahmah; Hasratuddin Hasratuddin (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to analyze the effectiveness of implementing the Realistic Mathematics Education (RME) model in enhancing students’ conceptual understanding and mathematical communication skills. The research method employed is a systematic literature review involving the collection, evaluation, and synthesis of data from academic sources such as journals, books, and scientific articles related to the RME model and Vygotsky’s learning theory in mathematics education contexts. The findings indicate that the implementation of the RME model significantly improves students’ conceptual understanding compared to conventional teaching methods. Moreover, the integration of Vygotsky’s theory supports the learning process through social interaction, which strengthens mathematical communication skills. The RME approach, which connects mathematics to real-world contexts, provides meaningful learning experiences that facilitate students in understanding and effectively communicating mathematical concepts. These results suggest that the RME model is a viable strategy for improving the quality of mathematics learning, particularly in conceptual understanding and communication skills.